GREATER RESISTENCIA STUDY CASE: GREENFIELD AND INCREASED DENSIFICATION - Malena Perez; Valeria Schneider (Universitas Muhammadiyah Jakarta, 2012)
ABSTRACT. This paper focuses on one of the relevant issues of the phenomena of urban expansion and densification, i.e. the lack of planning of public greenfields. At the regional level, since 2001, Resistencia City Council has been promoting a growth in height by increasing built-up areas in central districts that have complete infrastructure, through the implementation of the Ordinance 5403/01 - high density. On the other hand, in the last 10 years the population growth of the city (16%) has been followed by an increase in the supply of open space per inhabitant (85%). However, this increase is not reflected in the inner city areas, where the higher population density is located. This paper aims to analyze and relate the results arising, so far, from the densification of central areas and its relationship with the availability of open space in central districts of Greater Resistencia City. Keywords: Increased densification, greenfield availability, environmental quality.